PENGARUH EDUKASI TERHADAP TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG PERILAKU PERSONAL HYGIENE PADA SAAT MENSTRUASI DI SMP SWASTA RK MAKMUR MEDAN - Yuliana Christin Meha; Rostime Hermayerni Simanullang (PT. Hasba Edukasi Mandiri, 2025)
Background: Adolescence is a transitional period between childhood and adulthood, characterized by biological and psychological growth and development. One of the signs that a girl has entered puberty is experiencing her first menstruation (menarche). The inability to maintain hygiene during menstruation can lead to risks such as reproductive tract infections, urinary tract infections, and others. Additionally, there is a connection to the risks of HIV infection, cervical cancer, and poor pregnancy outcomes. To enhance adolescents' knowledge about menstrual hygiene and protect them from health impacts, it is important to provide them with information on menstrual hygiene. This information can be delivered through innovative and engaging health education. Objective: To analyze the effect of education on the knowledge level of adolescent girls regarding personal hygiene practices during menstruation at RK Makmur Junior High School, Medan. Method: This type of research is quantitative with a quasi-experimental design using the untreated control group design with dependent pretest and posttest samples. The sampling technique employed was proportionate random sampling, with a total of 73 respondents. The data analysis was conducted using the Wilcoxon signed-rank test. Results: The results of this study indicate that there is a significant effect of education on the knowledge level of adolescent girls regarding personal hygiene practices during menstruation, with a p-value of 0.00 < 0.05. conclusion: There is a significant effect of education on the knowledge level of adolescent girls regarding personal hygiene practices during menstruation at RK Makmur Junior High School, Medan, in 2024. Advice : For future research, it is recommended to conduct follow-up studies involving demonstrations using mannequins or other teaching aids to help adolescent girls better understand and accurately remember the correct actions for practicing personal hygiene during menstruation.